2005
DOI: 10.1007/s10796-005-1486-z
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Use Contexts in the Mobile Internet, Focusing on the Usability of Information Architecture

Abstract: The mobile Internet-accessing the Internet via a mobile device-has become quite popular recently. The mobile Internet is mainly different from the stationary Internet because it may be used in various contexts, whereas the stationary Internet is mostly used in pre-determined environments. However, it is unclear when the mobile Internet is used most frequently, and in what context it is most useful. A greater understanding of the contexts for using the mobile Internet will relieve usability problems that mobile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 22 publications
3
38
0
8
Order By: Relevance
“…It was indicated that perceived usefulness along with perceived ease of use is the most influential indicator of IT adoption (Hong and Tam 2006). Several studies of MI services demonstrated the direct or indirect influence of usefulness perception in forming behavioral intention for their adoption (Hong and Tam 2006;Kim et al 2005;Mao et al 2005). Meanwhile, according to the industry report from Internet Statistics Information System (ISIS) (2002), almost 31% of survey respondents indicated that they did not use MI because it was not a necessity, implying the distinctive bearing of usefulness perception in promoting MI usage.…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…It was indicated that perceived usefulness along with perceived ease of use is the most influential indicator of IT adoption (Hong and Tam 2006). Several studies of MI services demonstrated the direct or indirect influence of usefulness perception in forming behavioral intention for their adoption (Hong and Tam 2006;Kim et al 2005;Mao et al 2005). Meanwhile, according to the industry report from Internet Statistics Information System (ISIS) (2002), almost 31% of survey respondents indicated that they did not use MI because it was not a necessity, implying the distinctive bearing of usefulness perception in promoting MI usage.…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…The results from the study performed by Kim, Jimwoo, & Yeonsoo (2005), indicate that the most common context for using mobile Internet is described as follows: participants have a hedonic goal, their emotional state is high, their legs are stopped, visual and auditory distractions were low, few people are around them, and their interaction is low. This is a different picture from the widely held belief that the mobile Internet would be used often while moving outdoors.…”
Section: On-the-movementioning
confidence: 99%
“…Even the discussion of the mobile Internet service quality has been limited to technology-or network-performance centric topics such as bandwidth, latency, jitter, packet loss, and usability of information architecture (Kim et al 2005;Wood and Chatterjee 2002). Thus, the quality of mobile Internet service should be discussed from the mobile Internet consumers' perspective, because prospective users of the mobile Internet service are customers rather than simply technology geeks.…”
Section: Introductionmentioning
confidence: 99%